Insulin/IGF signaling drives cell proliferation in part via Yorkie/YAP - Straßburger, Katrin; Pinna, Federico; Breuhahn, Kai; Teleman, Aurelio A. (Developmental biology, 2012)
The insulin/IGF signaling (IIS) pathway is a potent inducer of cell proliferation in normal development and in cancer. The mechanism by which this occurs, however, is not completely understood. The Hippo signaling pathway regulates cell proliferation via the transcriptional co-activator Yorkie/YAP, however the signaling inputs regulating Hippo activity are not fully elucidated. Here we present evidence linking these two conserved, oncogenic pathways in Drosophila and in mammalian cells. We find that activation of IIS and of Yorkie signaling correlate positively in hepatocellular carcinoma. We show that IIS activates Yorkie in vivo, and that Yorkie plays an important role in the ability of IIS to drive cell proliferation. Interestingly, we also find the converse—that Yorkie signaling activates components of the insulin/TOR pathway. In sum, this crosstalk between IIS and Yorkie leads to coordinated regulation of these two oncogenic pathways.